CLASSIFICATION OF FUNDAMENTAL HUMAN RIGHTS. RIGHT TO LIFE - Teona Giorgadze (European Scientific Journal, ESJ, 2013)
The research of Human rights, their genesis, social roots has always been and remains an important problem during the mankind's historical development and continues to be the political, legal, or philosophical subject of the research. Human rights are being formed and developed with the development of mankind. The first codified laws, which include human rights norms, "Laws of Hammurabi", were established as early as 4000 years ago. It consisted of 282 laws and law was an unprecedented phenomenon in the ancient period of law artifacts, it is also considered to be the first version of the Code and contains the human rights norms.From the principles and purposes of the laws of Hammurabi, it is expressed that human rights do not have anything in common with the content of the present human rights, but the existence of these laws played a major role in the development of the justice system. From the beginning, they were the development, refinement, improvement and harmonization of the justice acts during the human history. Human rights have an important place in the international treaties and conventions.